PENGARUH LAMA FERMENTASI DAN JENIS GULA TERHADAP KADAR ALKOHOL MINUMAN BERBAHAN DASAR GANDARIA (Bouea macrophylla Griff) - Tuapattinaya, Prelly; Papilaya, Pamela Mercy; Tibalilatu, Anthonia R.O (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: Alcoholic beverages can be derived from palm sap or fruit juice. The fruit most widely used as a base for alcoholic beverages by the fermentation is generally grapes. The Gandaria (Bouea macrophylla Griff) can be used as raw material for substitute grapes for the process of making alcoholic beverages. Sugar is one of the important factors, because sugar is fermented by yeast into ethanol and CO2. The purpose of this research was to know the effect of fermentation time and types of sugar on alcohol content in gandaria(Bouea macrophylla Griff)-based drinks and organoleptic tests as a support for practicum in Ethnobotany courses. Methods: The research was conducted on 13 February-06 March 2023 at the Basic Chemistry Laboratory FMIPA and used destilation method. Results: The results showed that the combination of fermentation time and sugar type gave a very significantly different effect on each treatment. This can be seen from the results of the Least Significant Difference test where every week there is an increase in alcohol content. While, the organoleptic test showed the level of liking of the colour with the highest score of 2.9 in treatment f3g1, for the odor with the highest score of 2.9 in treatment f3g2 and for the taste with the highest score of 3.6 in treatment f2g1. Conclusion: Based on the results of the study, it was concluded that the time of fermentation and the type of sugar influenced the alcohol content of gandaria (Bouea macrophylla Griff). -based drinks